Solder Joint Reliability - Ricky Lee, S. W. (Soldering and Surface Mount Technology., 2004)
The decision to move to lead-free solders has been made, but processing and performance challenges remain. This paper considers the transition in terms of performance, with particular emphasis on long term, high reliability applications. Comparison of key mechanical properties indicates generally beneficial outcomes of the transition to lead-free alloys, although there is a lack of understanding surroundingˆanomalous'' observations, such as the effects of the bismuth. The lower melting point of Sn-Zn-Bi alloys, together with their comparable mechanical properties, provide further impetus to ad.